Tracking global economic uncertainty: Implications for the euro area - Alina Bobasu; André Geis; Lucia Quaglietti; Martino Ricci (European Central Bank (ECB), 2021)
This paper sheds light on the impact of global macroeconomic uncertainty on the euro area economy. We build on the methodology proposed by Jurado et al. (2015) and estimate global as well as country-specific measures of economic uncertainty for fifteen key euro area trade partners and the euro area. Our measures display a clear counter-cyclical pattern and line up well to a wide range of historical events generally associated with heightened uncertainty. In addition, following Pier and Podstawski (2018), we estimate a Proxy SVAR where we instrument uncertainty shocks with changes in the price of gold around specific past events. We find that, historically, global uncertainty shocks have been important drivers of fluctuations in euro area economic activity, with one standard deviation increase in the identified uncertainty shock subtracting around 0.15 percentage points from euro area industrial production on impact.
Keywords: D81; C11; C55; E32; F41; F62; 330; Uncertainty; Forecast Errors; Stochastic Volatility; Proxy SVAR; Economic Activity